2020
DOI: 10.1002/wrna.1628
|View full text |Cite
|
Sign up to set email alerts
|

Translational control in aging and neurodegeneration

Abstract: Protein metabolism plays central roles in age‐related decline and neurodegeneration. While a large body of research has explored age‐related changes in protein degradation, alterations in the efficiency and fidelity of protein synthesis with aging are less well understood. Age‐associated changes occur in both the protein synthetic machinery (ribosomal proteins and rRNA) and within regulatory factors controlling translation. At the same time, many of the interventions that prolong lifespan do so in part by pre‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 235 publications
(323 reference statements)
0
12
0
Order By: Relevance
“…During aging, the global translation rate decreases as the translation machinery becomes less efficient. This decrease is due to the deregulation of the stoichiometry of translation components that affects the abundance of ribosomes (Dhondt et al 2017; Janssens et al 2015) but also the rate and accuracy of translation (Gonskikh and Polacek 2017; Skariah and Todd 2021). Therefore, the age-dependent enrichment of ribosome components might affect protein homeostasis and promote a loss of proteostasis, one of the primary hallmarks of aging.…”
Section: Discussionmentioning
confidence: 99%
“…During aging, the global translation rate decreases as the translation machinery becomes less efficient. This decrease is due to the deregulation of the stoichiometry of translation components that affects the abundance of ribosomes (Dhondt et al 2017; Janssens et al 2015) but also the rate and accuracy of translation (Gonskikh and Polacek 2017; Skariah and Todd 2021). Therefore, the age-dependent enrichment of ribosome components might affect protein homeostasis and promote a loss of proteostasis, one of the primary hallmarks of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell transcriptomic analysis revealed that the expression level of eEF1A1 in neurons was low and changed with age in glial cells ( Ximerakis et al, 2019 ). Therefore, eEF1A may represent a potential candidate for lifespan modulation ( Skariah and Todd, 2020 ). In addition, eEF1A, along with eEF2, has been shown to be related to neurodegenerative disorders including Alzheimer disease (AD) and Parkinson disease (PD) with an unknown mechanism.…”
Section: Factors Involved In Aa-trna Incorporationmentioning
confidence: 99%
“…In addition, eEF1A, along with eEF2, has been shown to be related to neurodegenerative disorders including Alzheimer disease (AD) and Parkinson disease (PD) with an unknown mechanism. The low expression levels of these factors in the brains of AD and PD patients indicating defects in the efficiency or fidelity of translation ( Li et al, 2005 ; Vera et al, 2014 ; Garcia-Esparcia et al, 2015 ; Beckelman et al, 2016 ; Skariah and Todd, 2020 ). eEF1A has chaperone-like activity ( Lukash et al, 2004 ) and may also be involved in antiviral response by interaction with Sgt1, a multifunctional protein ( Novosylna et al, 2015 ).…”
Section: Factors Involved In Aa-trna Incorporationmentioning
confidence: 99%
“…Within the context of an aging neuronal environment, the accumulation of expanded repeat containing RNA and proteins could trigger cascades of events that affect both arms of the peptide life cycle—synthesis and degradation—precipitating neurodegeneration 32 …”
Section: Figurementioning
confidence: 99%